Teori Belajar Dalam Al-Qur’an - Ranowan Putra (Departement of Mathematics Education, 2024)
This research aims to discuss the conception of Islamic education in the Qur'an. The method used is a literature review, collecting data by searching for sources and constructing from various sources such as books, journals, and existing research. This text attempts to uncover the theories of learning found in the Qur'an. Learning is a conscious effort to improve abilities or behaviors by acquiring knowledge, skills, values, and certain attitudes. In essence, learning is a process of acquiring knowledge, enhancing skills, improving behavior, attitudes, and strengthening personality. Theories of learning in general include cognitive, behaviorist, constructivist, humanistic, and cybernetic theories. As for learning theories according to the Qur'an, they include Surah An-Nahl/16:78, An-Nisa/4:9, Al-Ghasyiyah/88:17-21, Az-Zumar/39:9, Al-Baqarah/2:256, and Al-Kahf/18:29. Theories of learning in general and learning theories according to the Qur'an are interconnected and equally play significant roles in teaching and learning activities, whether in terms of general knowledge or specific knowledge (Islam). Until now, both theories are still being used and rapidly evolving, both in formal education and non-formal education environments. The goal is to guide and direct learners so that they are able to master the rapidly evolving knowledge and technology, which inevitably includes the teachings of Islam, namely the Qur'an and Hadith.